2015
DOI: 10.14720/aas.2015.105.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of agro-morphological traits in promising hybrids of sunflower (Helianthus annuus L.)

Abstract: The main objective underlying sunflower breeding programs is to develop high-yielding productive F 1 hybrid cultivars. This study was conducted to investigate the genetic control of some agro-morphological traits of new sunflower F 1 hybrids. For this purpose, fourteen inbred lines of sunflower were crossed with three male sterile inbred lines. Their hybrids (14 hybrids) were then evaluated against three control cultivars. The data thus obtained were analyzed using the nested model (North Carolina Design І) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Distinct clustering pattern in sunflower, wherein CMS and restorer lines clustered separated from each other illustrating a different evolutionary pathway for each type (Lochner, 2011 ; Avin et al, 2013 ). Clustering of genotypes into different groups was based on their specific characteristics ( Table 2 ) (Kholghi et al, 2011 ; Shamshad et al, 2014 ; Golabadi et al, 2015 ). Genotypes that were early in the flowering were taller, larger in head size, high hundred seed weight, and produced more seed yield than those that were late in flowering thus having less time for seed development and filling, consequently leading to low seed yield.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct clustering pattern in sunflower, wherein CMS and restorer lines clustered separated from each other illustrating a different evolutionary pathway for each type (Lochner, 2011 ; Avin et al, 2013 ). Clustering of genotypes into different groups was based on their specific characteristics ( Table 2 ) (Kholghi et al, 2011 ; Shamshad et al, 2014 ; Golabadi et al, 2015 ). Genotypes that were early in the flowering were taller, larger in head size, high hundred seed weight, and produced more seed yield than those that were late in flowering thus having less time for seed development and filling, consequently leading to low seed yield.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation revealed differences in resistance levels among a large‐scale garlic germplasm and identified resistant resources. Cluster analysis based on morphological traits of genetic resources facilitate breeding based on an understanding of the germplasm and the selection of potential material among a large‐scale accession with high efficiency, as shown in studies of the genetic resources of many crops, including horticultural crops such as pepper, cowpea, watermelon, brassica, radish, and garlic . In this study, we used cluster analysis to classify 213 accessions of garlic collections into six groups, including HR, R, MR, MS, S, and HS, according to the pest index, facilitating the identification of resistance among the germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The non-additive gene effects have been previously identified governing the inheritance of important traits such as leaf area, specific leaf weight, leaf area index, leaf water potential, relative leaf water content, photosynthetic efficiency, proline content, seed yield, harvest index and oil content under normal and water limited growth regime [23,51,52]. Specifically, dies an early study, reported non-additive gene action for seed yield and oil content while additive gene action for oil content [53].…”
Section: Discussionmentioning
confidence: 99%